Perilaku Minat Wisatawan Terhadap Ekowisata Hutan Mangrove Baros Bantul - I Putu Hardani HD (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2019)
Abstract - The purpose of this study was to determine the behavioral interest of tourists who visited the Baros Bantul Mangrove Forest Ecotourism destination. To this end, field surveys have been carried out on the Baros Bantul Mangrove Ecotourism Center as a center for ecotourism for Mangrove Forests in Bantul. The survey was received from 100 participants consisting of tourists visiting the Baros Bantul Mangrove Forest Ecotourism. After the analysis, an assessment of the interest of tourists in the area was carried out. Research findings The need to develop a program of development activities that combines the potential of nature and culture to attract more tourist visits Introducing and promoting the tourism potential of Baros Mangrove, Development of facilities and infrastructure, Increasing the capacity of human resources in the local community in managerial training and technical training on welcoming tourists and Improving access to the Mangrove Tourism Baros Bantul Keywords: Ecotourism Tourist Visits, Interests, Visitors, Baros Bantul Mangrove Ecotourism Abstrak – Tujuan penelitian ini adalah untuk mengetahui perilaku minat wisatawan yang mengunjungi tujuan Ekowisata Hutan Mangrove Baros Bantul. Untuk tujuan ini, survei lapangan telah dilakukan di Ekowisata Hutan Mangrove Baros Bantul sebagai pusat ekowisata Hutan Mangrove di Bantul . Survei diterima dari 100 peserta yang terdiri atas wisatawan yang berkunjung ke Ekowisata Hutan Mangrove Baros Bantul . Setelah analisis, dilakukan penilaian tentang minat wisatawan di daerah tersebut. Temuan penelitian Perlunya mengembangkan program kegiatan pengembangan yang menggabungkan potensi alam dan budaya untuk ;lebih menarik minat kunjungan wisatawan. Mengenalkan dan mempromosikan potensi wisata Mangrove Baros, Pengembangan sarana dan prasarana, Peningkatan kemampuan SDM masyarakat lokal dalam pelatihan manajerial dan pelatihan teknis penyambutan wisatawan serta Pebaikan akses menuju ke Wisata Mangrove Baros Bantul Kata kunci: Perilaku Kunjungan Wisatawan Ekowisata, Minat, Pengunjung, Ekowisata Hutan Mangrove Baros Bantul